Investigation of Dendrimer-based nanoparticles cellular uptake and cell tracking in a semiautomated microfluidic platform - Carvalho, Mariana Rodrigues (2016)
A microfluidic device such as Kima Pump and Vena8 biochip is able to realize functions that are not easily imaginable in conventional biological analysis, such as highly parallel, sophisticated high-throughput analysis and single-cell analysis in a well-defined mannerÂ [1]. Cancer cell tracking within the microfluidic model will be achieved by grafting fluorescent label probe Fluorescein-5(6)-isothiocyanate (FITC) to dendrimer nanoparticles allowing cell visualization by immunofluorescent staining followed by fluorescence microscopy. In this study, synthesis and physicochemical characterization of Carboxymethyl-chitosan/poly(amidoamine) dendrimer nanoparticles (CMCht/PAMAM NPâ s) were performed[2]. Â Several cancer cell lines such as a HeLA (cervical carcinoma cell line), HTTC-116 (Colon Carcinoma) and Glioblastome cell line (GBM) were exposed to different concentrations of CMCht/PAMAM dendrimer nanoparticles over a period of 7d. After finding the adequate NP concentration, the internalization efficiency was tested, as well as cellular trafficking, in static and dynamic conditions (Kima Pump bioreactor).